Coping tendencies play partial mediating role between social support and anxiety/depression among Chinese keloid patients - Huang, Yuting; Xu, Shu; Wu, Yuqi; Gu, Zhifeng; Dong, Chen; Zhang, Li; Chen, Xiaodong (Frontiers in Psychiatry, 2025)
BackgroundIn addition to producing pain and itching, keloids can cause psychological symptoms, including anxiety and depression. We aimed to investigate the prevalence and underlying factors of anxiety/depression in Chinese keloid patients and to explore the mediating role between social support and anxiety/depression.MethodsA total of 202 self-reported questionnaires were collected from keloid patients, including the General Information Questionnaire, Vancouver Scar Assessment Scale (VSS), Patient and Observer Scar Assessment Scale (POSAS), Dermatological Problems Quality of Life Inventory (DLQI), Social Support Rating Scale (SSRS), Simple Coping Styles Scale (SCSQ), Self-Efficacy Scale (GSES) and the Hospital Anxiety and Depression Scale (HADS).ResultsThe mean scores for anxiety and depression were 9.82 ± 2.20 and 7.96 ± 2.70, respectively. Annual income (OR = 0.258), GSES score (OR = 0.2955), pain symptoms (OR = 1.281) and coping styles (OR:3.321) were significantly associated with HADS anxiety in keloid patients (P<0.05), whereas use of support (OR = 0.607) was significantly associated with HADS depression in keloid patients (p<0.05). The area under the curve (AUC) for the combined anxiety ROC for annual income, coping styles, pain symptoms and GSES scores was 0.835. PROCESS analysis concluded that coping tendencies partially mediated the relationship between social support and depression, with the mediating effect accounting for 38.58% of the total effect.ConclusionCoping tendency in keloid patients played a partial mediating role between social support and depression. Future studies should further explore how training in coping tendencies can enhance the effectiveness of social support to more effectively prevent and reduce depressive symptoms.